Comparative Indicators Of Credit Risk And Operational Risk Of Pt. Indonesian Sharia Bank Tbk Nationally: A Comparison Of Credit Risk And Operational Risk Of Pt. Indonesian Sharia Bank - Dean Amri, Ary; Rizki Thoyyibah, Rahmah; Aini, Mahsuri; Novita, Elma; Anggraini, Putri (Universitas Islam Lamongan, 2023)
This research aims to see the comparison of credit and operational risks of PT. Indonesian Sharia Bank nationally. The variables used in this research are credit risk (X1), operational risk (X2), and PT. Indonesian Sharia Bank (Y). This research method uses a mix method. The data sources used in this research are secondary data originating from the Financial Services Authority website and other supporting data from various print and electronic media related to this research. Data analysis used the Paired T-Test using SPSS 27.0.